(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Web application developers are increasingly advised to adopt an object-oriented programming (OOP) approach due to the growing complexity of application development and the related requirement to efficiently manage resources. While current design practises and development environments abstract away from the details of implementation technology, are not exceptionally versatile and performs a mid-reasonable job of planning for potential future upgrades or retention. This research is an attempt to screen out the significance and influence of OOP in web applications. Contextual research has been performed and the descriptive study has been discussed for the insights. Insight into the features, techniques, and efficient ideas of web application development is provided in this research work.